"Is it Hard Out Here for a Player?": Understanding the Relationship Between Adverse Childhood Experiences and Athletic Identity Among College Student Athletes - Courtney Copeland; Amy Reynolds; Jessica Ackley (University of Kansas Libraries, 2024)
It is unclear what impact, if any, early experiences with trauma may have on athletic identity. Athletic identity may serve as a protective shield for those who have adverse childhood experiences. Self-identifying as an athlete as opposed to the identity that experienced the trauma could be a defense mechanism for self-protection. The primary purpose of this exploratory study was to investigate the relationship between adverse childhood experiences and athletic identity as well as determine any influence from gender, ethnicity, and sport in a group of college athletes. Using Qualtrics software, 102 collegiate athletes currently enrolled in higher education institutions across varying NCAA divisions within the United States completed three measures: Personal Data Form, Athletic Identity Measurement Scale (AIMS), and Adverse Childhood Experiences Survey (ACES). Results found adverse childhood experiences were not significantly associated with Athletic Identity. However, results did show a difference between men and women, with a significant relationship between adverse childhood experiences and athletic identity in men but not women. Upon further examination, it was found that for men, consideration of ethnicity in conjunction with gender highlighted an even stronger relationship among Black men specifically. Implications for these findings, suggestions for university athletic departments, and recommendations for future research were made.